Business Analysis Of Procurement Process In Outsourcing Service Provider Business Unit (Jakarta Unit 2) - Giras Satria Kurniawan Putra; Siti Nursyamsiah (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted in conjunction with an internship program conducted at Business Unit 2 of the Outsourcing Provider, from February 20, 2023 to July 7, 2023. This study aims to analyze the implementation of the procurement business process in the unit. The research method used is a descriptive qualitative approach, which aims to understand the phenomena that occur in the object being studied. The data collected includes primary and secondary data; secondary data in the form of work documents such as Organizational Structure, Job Description, SOP, and work reports, while primary data is obtained through observation and interviews. The snowball sampling method was applied, where respondents were interviewed until the researcher felt that they had obtained sufficient information about the implementation of the procurement business process in three business units (BPO, MPO, KPO) in Business Unit 2 of the Outsourcing Provider Jakarta. The results of the study showed that the implementation of the three business units was in accordance with the existing SOP and could be relied on by partner companies.